Kajian Tingkat Kebisingan di Kawasan Rumah Sakit RSUD Sidoarjo di Masa Pandemi - Maritha Nilam Kusuma; Dita Risti Fadhilah (Jurnal Teknologi Lingkungan, 2022)
Noise in the hospital has a negative impact on patients. According to the data obtained, the patient category is most affected by high noise levels, namely 31% reporting that elderly men are the most affected, while around 27% indicate that elderly women are the most affected, then 14% think that children are the most affected by noise. The impact can be in the form of reduced sleep time and disruption in the treatment process. Therefore, an analysis of the noise level in the hospital is carried out along with its mitigation as noise management in Sidoarjo Hospital. This noise level measurement was carried out for five days using a Sound Level Meter (SLM) measuring instrument with four sampling points. Then calculate the equivalent noise level (Leq), then calculate the daytime noise level (Ls), and finally do the mapping using Surfer software and recommend noise level mitigation in the hospital. The results showed that the noise level still exceeds the quality standard. On Wednesday, the noise level value is 69.59–76.21 dBA, Thursday 68.7–77 dBA, Friday 68–70.89 dBA, Saturday 72.91–79.68 dBA, and Sunday 70–74.73 dBA. Recommendations for mitigating noise reduction in hospitals are with the planting Durante repens, Casia siamea, Heliconia sp., and Vermenia obtusifolia.